Association of fixed partial denture and gingival prosthesis as alternative approach to recover esthetics and function in anterior maxillary region - Ajita, Cristiane Okano; Anchieta, Rodolfo Bruniera [UNESP]; Martin, Manoel; Archangelo, Carlos Marcelo; Gil, Naiara Reis; Bertoncelo, Carlos Alexandre; Nesello, Daniela Garcia (Japan Prosthodontic Society, 2012)
Tooth replacement in the maxillary anterior region is especially difficult when the loss includes significant amounts of the residual ridge and the soft tissue. Several techniques are available, such as dental implants or fixed partial denture, and bone and gingival grafts or gingival prostheses, respectively. This article showed a clinical case of an elderly who was treated with a collarless metal-ceramic fixed partial denture and acrylic removable gingival prosthesis to recover the esthetics in the maxillary anterior region. The association of a metal-ceramic fixed denture and gingival prosthesis was an excellent alternative in cases when surgical procedures are contraindicated. © 2012 Japan Prosthodontic Society.
Keywords: Gingival prosthesis; Metal-ceramic fixed partial denture; Prosthodontics